The interlanguage development in the spanish learning as foreign language in Teletandem under the View of the Complexity Theory - Oyama, Andressa Carvalho Silva [UNESP] (Universidade Federal de Minas Gerais, Faculdade de Letras, 2013)
This article presents, under the perspective of Complexity Theory, the characteristics of the learning process of Spanish as a foreign language in Teletandem. Data were collected from two pairs of Portuguese-Spanish interagents, who were engaged in a systematic and regular interaction, based on the tandem principles. It was found that the learning experience is developed with the peculiarities that arise from the context, agents, members and their nuances, which revealed the presence of a shallow space between the systems of native and foreign languages.

O artigo apresenta, sob o prisma da Teoria da Complexidade, as características do processo de aprendizagem de espanhol como língua estrangeira em Teletandem. Foram coletados dados de dois pares de interagentes português-espanhol, que travaram uma interação regular e sistemática, baseada nos princípios tandem. Verificou-se que a experiência de aprendizagem se desenvolve com peculiaridades decorrentes do contexto, agentes, elementos e suas nuanças, o que revelou a presença de um espaço raso entre o sistema da língua materna e o da língua estrangeira.
O desenvolvimento da interlíngua na aprendizagem de espanhol como língua estrangeira em Teletandem sob a ótica da Teoria da Complexidade
Keywords: Complexidade; Teletandem; interlíngua; Complexity; Teletandem; interlanguage